SMART: a system of augmented reality for teaching 2nd grade students - Freitas, Rubina (2020)
In this paper, we describe the design and evaluation of SMART, an educational system that uses augmented reality for teaching 2nd grade-level concepts, adequate and integrated with national curriculum guidelines. SMART puts children exploring concepts like means of transportation, types of animals and similar semantic categories through the use of a set of racquets that are used to manipulate a TV-show style game with 3D models which are superimposed to the real time video feed of the whole class. Experiments were performed with several classes of students in three different, local primary schools. Results suggest that SMART is effective in maintaining high levels of motivation among children, and also that SMART has a positive impact on the students’ learning experience, especially among the weaker students.